Attachment of Giardia lamblia trophozoites to a cultured human intestinal cell line. Issue 4 (October 1995) - Katelaris, P H; Naeem, A; Farthing, M J
Abstract : Attachment of Giardia lamblia trophozoites to enterocytes is essential for colonisation of the small intestine and is considered a prerequisite for giardia induced enterocyte damage. The precise mechanisms involved are still being debated and some earlier work has been performed in models of uncertain biological relevance. In this study, co-incubation of giardia with enterocyte-like differentiated Caco-2 cells was used as a model to study the influence of physical and chemical factors on attachment. Giardia attachment was maximal between one and eight hours and stable over pH 7.2-8.2 but it was reduced by acidification. Attachment was dependent on temperature and was maximal at 37 degrees and virtually abolished at 4 degrees C. It was reduced compared with controls (p < 0.05) by EDTA 2.5 mM (mean (SEM) 32 (4)%), colchicine 12.5 microM (35 (5)%), mebendazole 10 micrograms/ml (30 (3)%), and cytochalasin B 1 microgram/ml (34 (3)%). Giardia attachment was also diminished by preincubation with mannose 50 mM or mannose-6-phosphate 35 mM (21 (4); 17 (5)%) or by preincubating Caco-2 cells with concanavalin A 100 micrograms/ml (19 (2)%). Enhanced binding was not evident after trypsinisation of trophozoites. Scanning electron microscopy showed that giardia seemed to attach to the Caco-2 monolayer predominantly by its ventral surface but dorsal orientation was also observed. No difference in attachment was observed between three different giardia isolates or a parent isolate and its clone. Attachment of giardia to Caco-2 cells is primarily by cytoskeletal mechanisms, inhibitable by interference with contractile filaments and microtubules, while attachment by mannose binding lectin also seems to mediate binding.